2003
DOI: 10.3168/jds.s0022-0302(03)73838-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corn Silage Particle Size and Cottonseed Hulls on Cows in Early Lactation

Abstract: The objective of this study was to evaluate the effects of reducing forage particle length (FPL) and the inclusion of cottonseed hulls (CSH) on intake, digestibility, chewing activity, and milk production of cows in early lactation. Sixteen multiparous cows averaging 17 ± 3 d in milk and 677 ± 58 kg BW were assigned to one of four 4 × 4 Latin squares. One square contained ruminally cannulated cows to evaluate effects of treatment on rumen fermentation and function. During each of the 23-d periods, cows were of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
47
7
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 39 publications
20
47
7
1
Order By: Relevance
“…In the current study, the daily mean ranged from 6.24 to 6.42 and from 4.00 to 4.50 for rumen pH and acetate/propio n a t e, respectively (Gencoglu and T u r k m e n , 2006). The percentages of milk fat in all diets were higher compared with those observed in other studies (Beauchemin et al, 2003;Kononoff and Heinrichs, 2003). In addition, these results are consistent with Mertens (1983) who reported that FCM yield was the greatest for cows fed diets based on AH, corn silage, or bermudagrass hay when dietary NDF content was 35% for each diet.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, the daily mean ranged from 6.24 to 6.42 and from 4.00 to 4.50 for rumen pH and acetate/propio n a t e, respectively (Gencoglu and T u r k m e n , 2006). The percentages of milk fat in all diets were higher compared with those observed in other studies (Beauchemin et al, 2003;Kononoff and Heinrichs, 2003). In addition, these results are consistent with Mertens (1983) who reported that FCM yield was the greatest for cows fed diets based on AH, corn silage, or bermudagrass hay when dietary NDF content was 35% for each diet.…”
Section: Resultssupporting
confidence: 82%
“…The requirement for peNDF of dairy cows was determined by Mertens (1997), who suggested that should be 22% of ration DM to maintain an average ruminal pH of 6.0 and 20% of ration DM to maintain the milk fat percentage of early to Midlactation Holstein cows at 3.4%. Based on measurements using the PSPS, several studies reported that increased intake of peNDF increased milk fat content (Yang et al, 2001;Kononoff and Heinrichs, 2003) and decreased milk protein content (Kononoff and Heinrichs, 2003), but others did not find any effects of peNDF on milk composition (Beauchemin et al, 2003;Kononoff et al, 2003b). Results obtained from the current study showed that cows fed with the CSW and CSWA diets had higher peNDF than CS and CSA (Table 2) but the peNDF did not affect the milk fat percentage.…”
Section: Resultsmentioning
confidence: 99%
“…Soita et al (2005) reported that 99% of corn silage retained when 1.18 mm sieve was used, and there was no difference between long (19.1 mm) and short (9.5 mm) cut corn silage. Similarly, no difference in PEF was found for long (22.3 mm) and short (4.8 mm) cut corn silage in the study by Kononoff & Heinrichs (2003b). Yang & Beauchemin (2006a) determined greater range in PEF using original PSPS with two sieves, than those obtained using three sieves (range of 0.41-0.72 vs. 0.93 to 0.96, respectively) for three theoretical cut length of corn silage (28.6, 15.9 and 4.8 mm).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, proportion of concentrate in the diets for different treatments was approximately 57% in DM basis. Reduced chop length of CS (Kononoff & Heinrichs, 2003b;Yang & Beauchemin, 2006a), and AH (Yang & Beauchemin, 2007) did not affect the dietary DM and NDF intake. It was discussed that the different dietary content of PENDF did not affect the rumen rate of digesta passage and thereby DM intake (Beauchemin & Yang, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation